Cis-acting Regulatory Elements in the Potato Virus X 3′ Non-translated Region Differentially Affect Minus-strand and Plus-strand RNA Accumulation - Pillai-Nair, Neeta (J Mol Biol, 2003)
The 72 nt 3′ non-translated region (NTR) of potato virus X (PVX) RNA is identical in all sequenced PVX strains and contains sequences that are conserved among all potexviruses. Computer folding of the 3′ NTR sequence predicted three stem-loop structures (SL1, SL2, and SL3 in the 3′ to 5′ direction), which generally were supported by solution structure analyses. The importance of these sequence and/or structural elements to PVX RNA accumulation was further analyzed by inoculation of Nicotiana tabacum (NT-1) protoplasts with PVX transcripts containing mutations in the 3′ NTR. Analyses of RNA accumulation by S(1) nuclease protection indicated that multiple sequence elements throughout the 3′ NTR were important for minus-strand RNA accumulation. Formation of SL3 was required for accumulation of minus-strand RNA, whereas SL1 and SL2 formation were less important. However, sequences within all of these predicted structures were required for minus-strand RNA accumulation, including a conserved hexanucleotide sequence element in the loop of SL3, and the CU nucleotide in a U-rich sequence within SL2. In contrast, 13 nucleotides that were predicted to reside in SL1 could be deleted without any significant reduction in minus or plus-strand RNA levels. Potential polyadenylation signals (near upstream elements; NUEs) in the 3′ NTR of PVX RNA were more important for plus-strand RNA accumulation than for minus-strand RNA accumulation. In addition, one of these NUEs overlapped with other sequence required for optimal minus-strand RNA levels. These data indicate that the PVX 3′ NTR contains multiple, overlapping elements that influence accumulation of both minus and plus-strand RNA.